Knowledge of sexually transmitted infections among health sciences students and teachers in southeastern Brazil - Diego P Scotini; Pedro HC Tomazelli; Michael S Miranda; Luiz G Elisei; Ehideé IG La-Rotta; Leonardo A dos Reis; Policardo G da Silva (Journal of Infection in Developing Countries)
Introduction: A cross-sectional study on the knowledge of sexually transmitted infections (STIs) was conducted. The objective was to assess the knowledge of STIs among health sciences students and teachers in a city in the southwest of Minas Gerais, Brazil.